Factor Analysis Affecting LOS in Yellow Triage Emergency Room at Bangil Hospital during the COVID-19 Pandemic - Firdaus Kristyawan; Nurdiana; Rinik Eko Kapti (International Journal of Science and Society, 2020)
Length of Stay (LOS) is a major problem that occurs in hospital emergency rooms because it needs quick and precise handling of its services, especially during the COVID-19 pandemic. LOS prolongation can lead to worsening of the patient's condition, increased costs, and mortality. Many factors cause LOS, but it is known that there several factors that affect LOS in the ER, including the duration of laboratory examinations, duration of radiological examinations, duration of specialist doctor consultation, and duration of the process of transferring patients in the ER. The aim of the study was to determine the most dominant factor and the big influence on LOS in the Bangil ER during the COVID-19. This research was a quantitative observational analytic with a cross-sectional approach that used LOS observation and a digital clock for recording. Participants were 109 patients who were admitted to the yellow triage IGD and received COVID-19 protocol. The results showed that there was a significant relationship between the duration of specialist doctor consultation and patient transfer process to LOS with a probability of 0.000 and then the duration of the patient transfer process is the most dominant factor compared the others with a beta value 0.625. The duration of the patient transfer is the most dominant factor in LOS. Further research could be focused on the specific disposition of inpatient or hospital discharge. Then regarding the pandemic, it is possible to examine variables related to COVID-19.